Case report: Immunotherapy-based combination therapy achieving complete remission and prolonged survival in nasopharyngeal carcinoma with extensive bone marrow metastasis - Wang, Xingran; Yuan, Ying; Zhang, Yan; Qiao, Guanglei; Chen, Shihong; Huang, Wentao; Zhang, Jianjun (Frontiers in Immunology, 2024)
Nasopharyngeal carcinoma with bone marrow metastasis presents a rare and challenging clinical scenario associated with exceedingly poor prognosis. While standard treatment regimens offer limited efficacy and tolerability in such cases, individualized approaches are increasingly necessary. We present the case of a 64-year-old male diagnosed with recurrent nonkeratinizing undifferentiated nasopharyngeal carcinoma with extensive bone marrow metastasis (rTxN0M1). Treatment was initiated with immunotherapy-based combination therapy, consisting of pembrolizumab and low-dose cisplatin, which resulted in an initial response. Subsequently, there was a transition to standard-dose nab-paclitaxel-cisplatin chemotherapy in combination with pembrolizumab, followed by maintenance therapy with pembrolizumab plus fruquintinib. The patient achieved a sustained response with renormalization of tumor markers, imaging findings, and bone biopsies, resulting in complete remission. This case highlights the successful management of nasopharyngeal carcinoma with extensive bone marrow metastasis through an individualized treatment approach incorporating immunotherapy.